IMPLEMENTASI METODE PROTOTYPE PADA PERANCANGAN APLIKASI PEMESANAN JASA JAHIT BERBASIS WEB PADA KORITA TAILOR - Aldo Hermawan Suryana; Muhammad Djafar; Roni Sefia; Roeslan Djutalov (Shofanah Media Berkah, 2023)
Ordering sewing services is a service sector UMKM whose existence is really needed by many groups, this happens because clothing or clothing is a basic human need, therefore sewing services are a business that is quite convincing and has a fairly long business life. In the research conducted on Korita Tailor, problems with the ordering system for sewing services were found, which only used conventional systems. It is said conventionally because they have not used communication facilities effectively and efficiently in ordering sewing services, for example by telephone. The Prototype Method is a software development method that allows for interaction between system developers and system users, so as to overcome incompatibilities between developers and users. From the results we got from this research, it really helps customers to order sewing services so they don't have to bother coming to the sewing place and can order indirectly.